Lamb mortality in a flock of East African Blackheaded sheep - Trail, J.C.M.; Sacker, G.D. (Cambridge University Press, 1966)
The effects of birth weight, sex, twinning, parity of dam and dry season on mortality rates of lambs were studied between births and weaning at 20 weeks in a flock of East African Blackhead sheep. The mean birth weight of non-surviving lambs was lower than those of surviving lambs. Singles from gimmers and twins from ewes were 0.5 and 1.0 lb., respectively, lighter at birth and had higher mortality rates than singles from ewes. The overall mortality rate of singles from ewes was 16%, singles from gimmers 20% and twins from ewes 28 %. Male and female lambs born alive had similar mortality rates (18 %). The maximum survival rate was found to occur among lambs with birth weights close to the mean. Mortality increased sharply at the lower extreme of lamb birth weights, but high birth weights did not bring increased mortality. No cases of difficult births were encountered, but perinatal mortality was lower in twins than in singles. Perinatal mortality accounted for 8 % of total losses, birth to 21-day mortality for 31% and 21-day to 20-weeks mortality for 61 %. Although dry season during pregnancy had no apparent effect on birth weights, there seemed to be somewhat higher mortality both over the birth to 21-days period and the birth to 20-weeks period among lambs whose dams had been exposed to dry conditions. Similarly lambs suckled under dry conditions showed apparently higher mortality rates than lambs suckled in the remainder of the year. The management practice of retaining lambs indoors for the first 3 weeks of life appeared to have a marked effect on lamb mortalitv.